Assessment of arsenic and vanadium pollution in surface sediments of the Egyptian Mediterranean coast. (1st January 2013) - Abdel Ghani, Safaa A.; Shobier, Aida H.; Shreadah, Mohamed A.
An assessment of arsenic and vanadium pollution was investigated for surface sediments collected from 41 sampling stations along the Egyptian Mediterranean coast during summer 2008. Grain size analysis, Total Organic Carbon (TOC), total silicate and carbonate contents were also studied. Concentrations of arsenic and vanadium were high especially in sediment samples collected from the eastern area of the coast. The arsenic contents in this area varied from 6.13 mg kg –1 to 89.21 mg kg –1 with an average value of 29.90 mg kg –1 ± 19.21 mg kg –1 . Meanwhile, vanadium concentrations varied from 25.04 mg kg –1 to 574.75 mg kg –1 with an average of 184.81 mg kg –1 ± 134.42 mg kg –1 . A strong correlation was observed between arsenic and vanadium, indicating their similar source. The main source of pollution is the offshore oil fields and industrial wastes. The TOC ranged between 0.2% and 1.8%, while total carbonate varied between 7.02% and 96%. Cluster analysis was applied to study the state of the investigated area.